Pharmacokinetics, Immunogenicity and Safety Study for SHR-1309 Injection and Perjeta® in Healthy Chinese Male Volunteers - Cui, Yingzi; Cui, Dongyang; Ren, Xinran; Chen, Xuesong; Liu, Guangwen; Liu, Zhengzhi; Wang, Yanli; Qu, Xinyao; Zhao, Yicheng; Yang, Haimiao (Frontiers in Pharmacology, 2021)
Abstract Objectives: Pertuzumab is a monoclonal antibody for the treatment of breast cancer. The aim of this study was to compare the pharmacokinetics, immunogenicity and safety of the test preparation SHR-1309 injecta and the reference preparation Perjeta® in healthy Chinese male subjects. Methods: In this randomized, double-blind, single dose, two-way, parallel bioequivalence trial, a total of 80 qualified Chinese male subjects were selected and randomly divided into two groups. Each subject was intravenously injected with SHR-1309 or Perjeta®. Blood samples were collected at 21 different time points for pharmacokinetic analysis. In addition, immunogenicity was assessed at 5 different time points. The safety of the medication was monitored throughout the whole trial. Results: Cmax and AUC0-t were the primary pharmacokinetic parameters. Under a 90% confidence interval, their geometric mean ratios were 98.30% and 88.41% for SHR-1309 injection and Perjeta®, respectively. The geometric mean ratio of secondary pharmacokinetic parameters AUC0-∞ was 88.58%. These evaluation indexes are in the standard range of 80% - 125%, so SHR-1309 can be considered bioequivalent to Perjeta®. After 1680 h (day 70)c of administration, the two groups had 12 and 13 subjects who produced antidrug antibody (ADA), respectively. The occurrence time and proportion of ADA in SHR-1309 and Perjeta® were similar between subjects, and they had similar immunogenicity. During the entire trial period, there were 71 drug-related adverse reactions in 29 subjects who received SHR-1309 and 61 drug-related adverse reactions in 32 subjects who received Perjeta®. The incidence of adverse reactions between the two drugs was similar. Conclusions: The pharmacokinetic parameters, immunogenicity and safety of the biosimilar SHR-1309 injection produced by Shanghai Hengrui Pharmaceutical Co. Ltd. were similar to the original drug Perjeta® produced by Roche Pharma AG. The two drugs met the bioequivalence evaluation criteria. Therefore, SHR-1309 is bioequivalent to Perjeta®. Clinical trial registration: CTR20200738